2008
DOI: 10.1029/2007gl031849
|View full text |Cite
|
Sign up to set email alerts
|

Causal link between Quaternary paleoclimatic changes and volcanic islands evolution

Abstract: Giant landslides and resulting tsunamis represent the main geologic hazards linked to volcanic island evolution. From offshore and onland studies, flank failures have been identified around numerous islands, in most geodynamic contexts. However, the triggering conditions are still poorly understood and several causes may act simultaneously to reach a critical threshold. Here we show that most large volume (>10 km3) landslides occur at glacial stages termination and we propose that a causal relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 45 publications
(78 reference statements)
0
62
0
2
Order By: Relevance
“…Los factores desencadenantes de los colapsos en islas oceánicas se agrupan en internos, asociados principalmente a la fuerza ascensional del magma (Siebert, 1984;Carracedo, 1994;Carracedo et al, 1998;McGuire, 1996;Elsworth & Day, 1999), y externos, relacionados en última instancia con agentes climáticos (McMurtry et al, 2004;Quidelleur et al, 2008). Obviamente hay una amplia casuística y se puede dar una combinación de factores desencadenantes.…”
Section: Factores Externos Desencadenantes De Colapsos Laterales Masivosunclassified
See 1 more Smart Citation
“…Los factores desencadenantes de los colapsos en islas oceánicas se agrupan en internos, asociados principalmente a la fuerza ascensional del magma (Siebert, 1984;Carracedo, 1994;Carracedo et al, 1998;McGuire, 1996;Elsworth & Day, 1999), y externos, relacionados en última instancia con agentes climáticos (McMurtry et al, 2004;Quidelleur et al, 2008). Obviamente hay una amplia casuística y se puede dar una combinación de factores desencadenantes.…”
Section: Factores Externos Desencadenantes De Colapsos Laterales Masivosunclassified
“…Estas observaciones en el Rift NE, junto con otras en Tenerife (colapso del Valle de Icod a 161 ± 13 - Gillot et al, 2001) y en otras Islas Canarias (La Palma, El Hierro- Carracedo et al, 1999b;Guillou et al, 2001), así como en otras islas oceánicas alrededor del mundo (Tahiti, Hawaii, Martinica, Guadalupe-McMurtry et al, 2004;Quidelleur et al, 2008) parecen tener en común que la interrupción de la estabilidad de grandes edificios volcánicos se produce en periodos interglaciales con elevados niveles del mar, preferentemente poco después de bruscas deglaciones. La disponibilidad de elevadas cantidades de agua en medios geológi-cos ya de por sí con elevada inestabilidad aceleraría e incrementaría el despegue de grandes masas de depósitos volcánicos.…”
Section: Factores Externos Desencadenantes De Colapsos Laterales Masivosunclassified
“…An aseismic movement of the Hilinia Slump system has been recorded with continuous GPS measurements and linked with a major rainfall event (Cervelli et al, 2002) so pore pressures are clearly important. Also suggesting links with pore pressure, Quidelleur et al (2008) put forward evidence for incidences of landslides occurring during glacial-induced eustatic sea-level change and Mitchell (2001Mitchell ( , 2003 outlined a transition in the morphology of edifices at > 2000 m height that may have a pore-pressure origin amongst other possibilites. Concerning links to intrusions, Clague and Denlinger (1994) suggested that the high density and weak rheology of hot olivine cumulates may contribute to the movement of the Hilina slump.…”
Section: Massive Failurementioning
confidence: 99%
“…The timing of collapse events correlates somewhat with glacial-induced eustatic sea-level change [100]. Furthermore, a transition occurs from small oceanic volcanoes, which rarely show evidence for flank collapse, and those taller than 2500 m, where collapse structures are common [101,102].…”
Section: (B) Volcanic Islandsmentioning
confidence: 95%